Peristalsis of Eyring-Powell magneto nanomaterial considering Darcy-Forchheimer relation - Hayat, Tasawar; Farooq, Shahid; Ahmad, Bashir; Alsaedi, Ahmed (International journal of heat and mass transfer, 2017)
•Peristalsis of Eyring-Powell is modelled.•Magneto nanofluid is considered.•Temperature dependent viscosity model is used.•Thermal radiation aspect is highlighted.•Newtonian heat and mass conditions are also accounted. The objective of current attempt is to address the impact of Darcy-Forchheimer relation and radial magnetic field on peristalsis of Eyring-Powell nanomaterial in a curved channel. The channel boundaries satisfy the velocity slip and Newtonian heat and mass conditions. The present analysis involves mixed convection, Brownian motion and thermophoresis. The modelled equations are satisfied subject to long wavelength and low Reynolds number. Numerical solution of dimensionless non-linear system is obtained by employing built-in shooting algorithm in Mathematica. Numerical solution for velocity, temperature and concentration are discussed for the sundry parameters of interest. Further graphical results indicate that velocity has opposite behavior for Darcy and Darcy-Frochheimer parameters. Velocity and temperature have shown reverse behavior for variable viscosity parameter. Temperature enhances while concentration has opposite results for both Brownian motion and thermophoresis parameters.